PENGARUH KEBIJAKAN HUKUM TERHADAP WAJIB PAJAK DAN FISKUS DALAM SYSTEM SELF ASSESSMENT - Akhmad Budiarto; Dudik DJ Sidharta (Media Bina Ilmiah, 2025)
Taxes are a primary source of funding for national development, and the government implements a Self-Assessment System to facilitate independent tax reporting by taxpayers. However, this system has not been fully effective, as evidenced by tax evasion cases such as in Decision No. 41/Pid.Sus/2023/PN Jkt Sel. This study aims to analyze the impact of tax law policy under the Self-Assessment System on taxpayers and tax authorities (fiscus), as well as to examine the judge's role in assessing the validity and truthfulness of the Tax Return (SPT) submitted in the aforementioned case. This normative legal research applies a statute approach and conceptual approach, using legal materials such as Law No. 7 of 2021 on the Harmonization of Tax Regulations, the Criminal Code (KUHP), and secondary sources from literature. The findings indicate that the Self-Assessment policy positively influences taxpayers by enhancing tax awareness, responsibility, independence, and trust in the government. For tax authorities, it improves administrative efficiency, reduces operational costs, focuses efforts on supervision and enforcement, encourages tax system modernization, and strengthens public trust. In judicial review, the judge's role includes examining the SPT based on actual conditions, evaluating its formal and procedural aspects, and considering it as valid evidence in tax disputes. The assessment is based on various forms of evidence, including witness testimony, expert opinions, documents, indications, and defendant statements. This study highlights the need for a balanced approach between taxpayer trust and firm legal enforcement.